Privilège frontalier et exercice corporatif, les métiers parisiens aux xviie et xviiie siècles - Mathieu Marraud (L'Atelier du CRH)
The efficacy of privilege under the Old Regime, especially as concerning the economy, is an oft-repeated postulate of historiography. The contexts in which it was used often came under the activities of the law or the police, and the privilege of guilds was far from being any exception. There were many struggles in activating these privileges, due to their near-permanent disputation, a disputation which constituted the very heart and the viability of corporatism. This is why we must investigate the application of these privileges. At the same time, without renouncing the idea their real efficacy, we must displace them to their own margins, their borders. At their outer limits, privileges stood in opposition to other trades, which were thus excluded from such and such a sector of sale or manufacture. This did not result in the application of norms and qualities to a finite set of merchandise and commercial positions. Rather, trade privileges were mainly aimed at precluding others from these same norms and qualities, the same merchandise and postures. Privilege also served to blur the indeterminate lines of demarcation concerning those same elements with regards to the holder of said privilege. Thus, we must look at this border as the site of a real social connection, where professional identities and individual careers were continually brought into play, and where, especially, the border between merchant/craftsman categories was constantly shifting.